Well-crystallized borax prepared from boron-bearing tailings by sodium roasting and pressure leaching. Issue 49 (15th June 2017) - Xie, Wei; Zou, Chengxi; Tang, Zhenyu; Fu, Hanguang; Zhu, Xukun; Kuang, Jiacai; Deng, Yingjun
Abstract : We report a low-cost and effective technique for preparing borax from boron-bearing tailings, which is at a low grade of 9.98% B2 O3 . Abstract : We report a low-cost and effective technique for preparing borax from boron-bearing tailings, which is at a low grade of 9.98% B2 O3 . Well-crystallized borax is achieved by the removal of impurity, evaporation and concentration through the efficient method of sodium roasting and pressure leaching. The morphology, composition and structure of borax are investigated in this study. The result of scanning electron microscopy shows that the crystals obtained are cube-shaped with smooth surface and of good growth. The crystals are proven to be Na2 B4 O7 ·10H2 O by EDS, XPS, XRD and ICP-AES. Moreover, the recovery rate of boron can reach 63.49%. This cost-effective strategy of preparing borax from boron-bearing tailings provides a guideline for the development of the boron industry and has a great potential for the commercialization of borax production.